2020
DOI: 10.1002/iid3.322
|View full text |Cite
|
Sign up to set email alerts
|

Cellular reactions in capillary and venous blood in northerners to a short‐term period in a climatic chamber

Abstract: The purpose is a comparative study of the cellular reactions in capillary and venous blood in northerners under general hypothermia in a climatic chamber during different photoperiods. The authors examined 108 relatively healthy people (80 women and 28 men aged 21-to 50-years old). Methods: The study included determining the hemogram, neutrograms, monocytograms, lymphocytograms, and phagocytic activity neutrophil granulocytes, enzyme immunoassay, flow cytometry, indirect immunoperoxidase, bioluminescence, syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Significant relationships have been reported regarding the number and percentage of CD4+, CD8+ T cells, CD20+ B cells, and ambient temperature, sunlight duration, and air pressure in healthy volunteers 30 . The systematic effect of general cooling by 5-min exposure to cold air at a temperature of − 25 °C in healthy volunteers leads to decrease of T-lymphocytes count in venous blood, which indicated their functional insufficiency 31 . Although it has been reported that environmental factors www.nature.com/scientificreports/ such as oxygen concentration 32,33 , acidification 34,35 , salt concentration 36 , and glucose, amino acid, and lipid metabolism [37][38][39] altered the differentiation and the function of immune cells, and contributed to the pathology of autoimmune diseases, it remains unclear how climatic factors such as air temperature and air pressure regulate immune cell function and the development of autoimmune diseases including RA.…”
Section: Discussionmentioning
confidence: 99%
“…Significant relationships have been reported regarding the number and percentage of CD4+, CD8+ T cells, CD20+ B cells, and ambient temperature, sunlight duration, and air pressure in healthy volunteers 30 . The systematic effect of general cooling by 5-min exposure to cold air at a temperature of − 25 °C in healthy volunteers leads to decrease of T-lymphocytes count in venous blood, which indicated their functional insufficiency 31 . Although it has been reported that environmental factors www.nature.com/scientificreports/ such as oxygen concentration 32,33 , acidification 34,35 , salt concentration 36 , and glucose, amino acid, and lipid metabolism [37][38][39] altered the differentiation and the function of immune cells, and contributed to the pathology of autoimmune diseases, it remains unclear how climatic factors such as air temperature and air pressure regulate immune cell function and the development of autoimmune diseases including RA.…”
Section: Discussionmentioning
confidence: 99%